O3-S5.03 High-dose valacyclovir decreases plasma HIV-1 levels more than standard dose acyclovir in HIV-1, HSV-2 positive persons: a randomised, crossover trial. (10th July 2011) - Perti, T; Baeten, J; Johnston, C; Diem, K; Ochbamichael, N; Huang, Meei-Li; Selke, S; Magaret, A; Corey, L; Wald, A
Abstract : Background: Standard doses of HSV suppressive therapy reduce plasma HIV-1 levels (0.25-0.5 log10 copies/mL) among HIV-1/HSV-2 co-infected persons, and modestly slow disease progression. Putative mechanisms for this effect include direct inhibition of HIV-1 by acyclovir or indirect reduction by decreasing HSV-associated inflammation. We hypothesised that higher-dose anti-HSV therapy would result in greater reduction in plasma HIV-1 RNA, and that the effect would be mediated by greater suppression of HSV shedding. Methods: 34 participants with HIV-1 and HSV-2 who were not on antiretroviral therapy were enrolled into a randomised, open-label cross-over trial with valacyclovir 1000 mg twice daily or acyclovir 400 mg twice daily for 12 weeks. After a 2 week wash-out, they were crossed over to the alternate treatment arm for 12 weeks. HSV PCR was performed on self-collected genital swabs obtained daily during the first 4 weeks of each treatment period. Plasma HIV-1 RNA was measured weekly throughout the study. Results: Among the 26 participants who completed both arms of the study, the mean age was 44; 21 were men. At entry, mean CD4 count was 525 cells/mm3 (range, 242–1055) and mean plasma HIV-1 RNA 3.9 log10 copies/ml (range 1.2–5.5). The mean plasma HIV RNA was 3.86 log10 copies/ml during acyclovir administration compared with 3.57 log10 copies/ml on valacyclovir; a 0.29 log10 copies/ml reduction (p=0.002). One week after initiation of valacyclovir, plasma HIV RNA decreased by a mean of 0.40 log10 copies/ml. Valacyclovir reduced HIV-1 RNA by ≥0.25 log10 copies/ml in 14 (54%) participants, compared with 3 (12%) on acyclovir. Neither the HSV shedding rate (8.92% vs 8.98% of days, p=0.94), nor the genital lesion rate (4.3% vs 1.1%; p=0.18) differed on acyclovir vs valacyclovir. Conclusions: High-dose valacyclovir reduces plasma HIV-1 RNA levels more effectively than standard dose acyclovir in HIV-1, HSV-2 seropositive persons not receiving antiretroviral therapy. High dose valacyclovir does not provide more potent suppression of HSV reactivation in HIV-1 infected persons than acyclovir, suggesting that the effect of valacyclovir on HIV-1 RNA may not be mediated via HSV suppression.